The Rulal game is used to facilitate natural resource governance in Southeast Asia and to train students in natural resource management - CGIAR Research Program on Policies, Institutions, and Markets (2019)
The Rulal board game developed by IWMI with support from PIM has been used by government agencies and civil society organizations in Lao PDR to demonstrate how power structure and relations influence decision making and negotiation processes on land use planning. Universities in Thailand and the Netherlands have included the game in courses on natural resource management.